“Melancholy Courage and Peasant Shrewd Cunning”: The Recruitment of Yugoslav-Canadians for Special Operations Executive Missions during the Second World War - Petrou, Michael (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2018)
During the Second World War, the British Secret Intelligence Service recruited more than thirty Yugoslav-Canadians to infiltrate the Balkans and liaise with resistance groups there as members of the Special Operations Executive. These men were immigrants and political radicals. Most were members of the Communist Party of Canada. Five had fought in the Spanish Civil War. They lived marginalized lives in Canada, were subject to police harassment and at risk of deportation. Yet their recruitment into an organization run by the British ruling class took place with the enthusiastic cooperation of the Communist Party of Canada. The party, and the recruits themselves, recognized that they shared with the British and Canadian governments a desire to fight fascism in Yugoslavia, and that, despite their divergent political ideologies, this common goal justified close and focused collaboration.